The prevalence and clinical significance of inhalant withdrawal symptoms among a national sample - Vaughn MG; Ahmedani BK; Glass JE; Perron BE; Roberts DE; Wu LT (Dove Medical Press, 2011)
Brian E Perron1, Joseph E Glass2, Brian K Ahmedani3, Michael G Vaughn4, Daniel E Roberts1, Li-Tzy Wu51University of Michigan, Ann Arbor, MI, USA; 2Washington University, St Louis, MO, USA; 3Henry Ford Health System, Detroit, MI, USA; 4St Louis University, St Louis, MO, USA; 5Duke University, Durham, NC, USABackground: Inhalants are among the most common and dangerous forms of substance use, but very little research on inhalant use disorders exist. Unlike other substances, the Diagnostic and Statistical Manual, 4th edition (DSM-IV) indicates that inhalants do not have an associated withdrawal syndrome among persons who meet criteria for inhalant dependence.Methods: Using data from the National Epidemiologic Survey on Alcohol and Related Conditions, this study examines the prevalence of withdrawal symptoms among inhalant users. Prevalence of inhalant withdrawal symptoms for inhalants was also compared with the prevalence of cocaine withdrawal symptoms to help determine the presence of an inhalant withdrawal syndrome.Results: Approximately 47.8% of persons who met criteria for inhalant dependence reported experiencing three or more inhalant-related withdrawal symptoms that were clinically significant. Among those with inhalant dependence, almost half of the withdrawal symptoms were as common as the corresponding withdrawal symptoms experienced by persons with cocaine dependence. Furthermore, the percentage of persons with inhalant dependence reporting clinically significant inhalant withdrawal symptoms was almost equal to the percentage of persons with cocaine dependence reporting clinically significant cocaine withdrawal symptoms.Conclusions: These data provide evidence for an inhalant-related withdrawal syndrome among persons with inhalant dependence. Revisions to DSM-IV should consider including inhalant withdrawal as a diagnostic criterion for this disorder.Keywords: Inhalants, volatile solvents, withdrawal, inhalant use disorders